Students’ perception of the enforcement model approach towards radicalism movement in Malaysia Higher Learning Institutions (HLI’s) - Alice Sabrina Ismail; Muhammad Mujtaba Habib (Penerbit Universiti Kebangsaan Malaysia, 2024)
Radicalism among undergraduates in a higher learning institution (is an HLI’s) thing that is already synonymous in most countries, especially in developing nations. The radicalism brought about by the student movement is not triggered, but it is often influenced by the issue of statehood, which is a factor in social change and the formation of community values. However, the involvement of students in higher learning institutions (HLI’s) in Malaysia is now not as intense and aggressive as in the foreign context. Based on scientific studies, student participation in Malaysia lack awareness and concern about the current political issues and problems around them. The enforcement of the University College University Act (AUKU) 1971 in Malaysia, which prohibits students from engaging in politics for five decades, has caused some passivity and paralysis in the students’ interest in political activities. Therefore, this study’s main objective is to develop a resilience model in preventing radicalism in a more student-friendly scenario that does not constrain students’ rights in Malaysia, like the Universities and University Colleges Act (AUKU), by benchmarking the good practices in Indonesia’s Higher Learning Institution (HLI’s) using the Altbach’s theoretical framework. Thus, questionnaires were conducted among students in three HLI’s – UTM, UKM and UM to understand students’ perception of AUKU from the technical and social sciences backgrounds. The study found that students’ perception of the AUKU enforcement model was poorly satisfactory and required a review, as universities function not as controlled factories but as generators of knowledge for producing great and intellectual national leaders regardless of their calibre and performance.